Impact of Chemical and Physical Pretreatment on Methane Potential of Peanut Shells - Armando Oliva; Stefano Papirio; Giovanni Esposito; Piet N. L. Lens (Energies, 2023)
The request for alternative sources of energy has led to evaluating untapped routes for energy production, such as using abundant and low-cost waste materials, e.g., lignocellulosic wastes, as the substrate for biological processes aimed at biofuel production. This study focused on peanut shells (PS) valorisation via anaerobic digestion (AD). Two emerging pretreatments, i.e., organosolv and ultrasounds, were investigated to unlock the full AD potential of PS. The impact of a substrate-to-solvent ratio in organosolv pretreatment was investigated (i.e., 1:5 vs. 1:10 vs. 1:20). Different exposure times were tested for ultrasound pretreatment, corresponding to applied energy densities of 30,000, 12,000, and 6000 kJ/kg VS, respectively. Organosolv pretreatment achieved the maximal polyphenol solubilisation, i.e., 4.90 mg/g TS, when increasing the substrate-to-solvent ratio, whereas methane production did not benefit from the pretreatment, being comparable with that of raw PS at most (i.e., 55.0 mL CH4/g VS). On the other hand, ultrasounds mainly affected sugar solubilisation (up to 37.90 mg/g TS), enhancing methane production up to an extra 64%, achieved with the highest energy density. The organosolv route would benefit from further downstream steps to recover the biomolecules released in the liquid fraction, whereas ultrasounds pretreatment provided a slurry suitable for direct AD.